Multiple Complex Chronic Conditions and Pediatric Hospice Utilization among California Medicaid Beneficiaries, 2007–2010 - Lindley, Lisa C. (J Palliat Med, 2017)
Background: Over 42,000 children die each year in the United States, including many with multiple complex chronic conditions (MCCCs), but little is known about whether the presence of MCCCs influences families to utilize pediatric hospice care. Objective: The study objective was to examine the relationship between MCCCs and pediatric hospice utilization among Medicaid beneficiaries. Methods: A retrospective, longitudinal cohort design was conducted with 2007–2010 California Medicaid data to examine the relationship between MCCCs (i.e., two or more MCCCs) and pediatric hospice utilization (i.e., hospice enrollment, hospice length of stay). Multivariate logistic regression with year fixed effects examined the effect of MCCCs on hospice enrollment, and negative binomial model with year fixed effects explored the relationship between MCCCs and hospice length of stay. Results: More than 10% of children enrolled in hospice care with an average length of stay of approximately three days. In the study sample, 48.6% of the children had MCCCs. MCCCs were not significantly related to hospice enrollment. However, children with MCCCs (incidence rate ratios = 4.25, p < 0.01) were associated with an increase in the number of days in hospice care. Conclusions: This study demonstrated that children with MCCCs have limited hospice care utilization at end of life. Future research is needed to explore barriers to hospice care for children with MCCCs.